Enhancing the Distribution of Idle Cost for Scheduling Tasks without Setup Cost in Cloud Computing - Al-dilami, Redwan A.; Zahary, Ammar T.; Al-Saqqaf, Adnan Z. (Hindawi, 2021)
Cloud computing uses virtualization to provide cost-effective computational resources to users. In task scheduling, idle cost may be distributed unfairly across tasks. This study proposes an enhanced algorithm for distributing idle cost when scheduling tasks without setup cost in cloud computing. The proposed method aims to reduce unfair cost allocation and improve cost distribution among scheduled tasks.